Application of GIS technologies to assess the impact on the surrounding environment of the location of wind power plants using the example of "Polonina Runa" of the Turye-Remetivskaya ah community - Peresoliak, V.; Radish, I.; Krylyo, I. (Land Management, Cadastre and Land Monitoring, 2025)
In the current context of renewable energy development, the most important task is to minimize the environmental impact of wind farms (WPPs) on the environment. The use of geographic information systems (GIS) allows for effective analysis and modeling of the impact of WPP placement, taking into account environmental, landscape, climatic and social factors. The article considers the use of geographic information systems (GIS) to assess the environmental impact of the location of a wind farm (WPP) on the territory of the "Polonyna Runa" tract of the Turye-Remetivka territorial community. The study involves the collection and processing of spatial data, including relief, wind speed and direction, the presence of protected areas and habitats of sensitive flora and fauna. GIS will be used to analyze visual and noise impacts, assess risks to biodiversity and public health, and model alternative siting options. The assessment results contribute to making informed decisions regarding the choice of a location for wind power plants, reducing negative environmental impact and ensuring a balance between the development of green energy and the preservation of the natural environment. Keywords: wind energy, environmental impact assessment, geographic information systems, spatial planning, sustainable development of territories, renewable energy sources, decarbonization, CO2 emissions.